Grzeczność językowa bohaterów filmu "Cudownie ocalony" w reżyserii Janusza Zaorskiego (system adresatywny) = Language politness of characters in the film "Cudownie ocalony" by Janusz Zaorski (adressative system) - Kresa, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The theme of the article is the adressative system characters in the film "Cudownie ocalony" by Janusz Zaorski, and its aim - to present the results of research on the determinants of linguistic politeness linguistic etiquette strategies in film dialogues.
Keywords: system adresatywny; język bohaterów filmowych; stylizacja; mediolingwistyka; adressative system; language of film heroes; stylisation; language of media